Human papillomavirus and posttransplantation cutaneous squamous cell carcinoma: A multicenter, prospective cohort study. Issue 5 (22nd November 2017) - Bouwes Bavinck, Jan N.; Feltkamp, Mariet C. W.; Green, Adele C.; Fiocco, Marta; Euvrard, Sylvie; Harwood, Catherine A.; Nasir, Shaaira; Thomson, Jason; Proby, Charlotte M.; Naldi, Luigi; Diphoorn, Janouk C. D.; Venturuzzo, Anna; et al.
Abstract : Organ transplant recipients (OTRs) have a 100‐fold increased risk of cutaneous squamous cell carcinoma (cSCC). We prospectively evaluated the association between β genus human papillomaviruses (βPV) and keratinocyte carcinoma in OTRs. Two OTR cohorts without cSCC were assembled: cohort 1 was transplanted in 2003‐2006 (n = 274) and cohort 2 was transplanted in 1986‐2002 (n = 352). Participants were followed until death or cessation of follow‐up in 2016. βPV infection was assessed in eyebrow hair by using polymerase chain reaction–based methods. βPV IgG seroresponses were determined with multiplex serology. A competing risk model with delayed entry was used to estimate cumulative incidence of histologically proven cSCC and the effect of βPV by using a multivariable Cox regression model. Results are reported as adjusted hazard ratios (HRs). OTRs with 5 or more different βPV types in eyebrow hair had 1.7 times the risk of cSCC vs OTRs with 0 to 4 different types (HR 1.7, 95% confidence interval 1.1‐2.6). A similar risk was seen with high βPV loads (HR 1.8, 95% confidence interval 1.2‐2.8). No significant associations were seen between serum antibodies and cSCC or between βPV and basal cell carcinoma. The diversity and load of βPV types in eyebrow hair are associated with cSCC risk in OTRs, providing evidence that βPV is associated with cSCC carcinogenesis and may present a target for future preventive strategies. Abstract : In two cohorts of organ transplant recipients, those with five and more different beta‐genus human papillomavirus types and high virus loads in eyebrow hairs subsequently develop significantly more cutaneous squamous cell carcinomas than others, suggesting that these virus types may increase the risk of cutaneous squamous cell carcinoma in these patients.